Rielle Navitski. Public Spectacles of Violence: Sensational Cinema and Journalism in Early Twentieth-Century Mexico and Brazil. Duke UP, 2017. - Ernesto R. Acevedo-Muñoz (Studies in 20th & 21st Century Literature, 2019)
Review of Rielle Navitski. Public Spectacles of Violence: Sensational Cinema and Journalism in Early Twentieth-Century Mexico and Brazil. Duke UP, 2017. xiv + 344pp.
Keywords: Navitski; R.; early cinema; Brazil; Mexico